Family therapies : a comprehensive Christian appraisal - Yarhouse, Mark A., 1968-; Sells, James Nathan, 1958- (Downers Grove, Ill. : IVP Academic, 2008)
"Christian therapists doing family therapy have never had a resource to help them navigate the various family therapy theories from a Christian perspective - until now. In this book Mark A. Yarhouse and James N. Sells survey the major approaches to family therapy and treat, within a Christian framework, significant psychotherapeutic issues. Calling for an integrated approach of "responsible eclecticism," they conclude with a vision for Christian family therapy. A landmark work providing critical Christian engagement with existing models of family therapy, this volume was written for those studying counseling, social work, psychology or family therapy. Family Therapies will also serve as an indispensable resource for those in the mental health professions, including counselors, psychologists, family therapists, social workers and pastors."--BOOK JACKET.
A Christian understanding for family therapy -- Historical foundations of family therapy -- Bowenian family therapy -- Strategic family therapy -- Structural family therapy -- Psychodynamic family therapy -- Contextual family therapy -- Experiential family therapy -- Solution-focused family therapy -- Cognitive-behavioral family therapy -- Narrative family therapy -- Toward an integrative Christian family therapy -- Crisis and trauma -- Attending to marital conflict -- Separation, divorce, and remarriage -- Individual psychopathology -- Substance abuse -- Gender, culture, economic class, and race -- Sexual identity -- Casting a vision for Christian family therapy.
Includes bibliographical references and indexes.
Keywords: Family psychotherapy -- Religious aspects -- Christianity; Psychology and religion; Family Therapy -- methods; Christianity; Religion and Psychology